Incremental dynamic analysis of woodframe buildings. - Christovasilis, Ioannis P. (Earthquake engineering & structural dynamics.)
The collapse of wood buildings was one of the main contributors to the heavy death toll and economic losses during the 1995 Hyogo-ken Nanbu (Kobe) earthquake in Japan. In California, half of the property loss from the 1994 Northridge earthquake was attributed to wood construction. Based on damage observed in recent earthquakes, the seismic vulnerability of existing wood buildings under maximum credible seismic events is uncertain. The main objective of this study is to quantify the seismic collapse fragilities and collapse mechanisms of a two-story townhouse and three-story woodframe apartment building through numerical analyses. Three construction quality variants (poor, typical and superior) were considered for each building in order to assess the effects of construction qualities on seismic collapse fragilities. The buildings were also re-designed according to the 2006 edition of the International Building Code to quantify the seismic fragilities of modern woodframe construction. The results obtained suggest that the construction quality, excitation direction and wall finish materials can influence significantly the collapse fragilities of woodframe buildings.